Quality control of cytotoxic infusions disturbed by a change of infusion bag: A case report. Issue 2 (April 2019) - Le Quinio, Pierre; Beiler, Benoît; Lider, Pauline; Demoré, Béatrice; Vigneron, Jean
Abstract: Introduction: In our centralized unit for the preparation of anticancer drugs, quality control is carried out by flow injection analysis (FIA) with detection by photodiode array detector. Criteria of concentration acceptance were established with ±10% of the theoretical concentration. The infusions were prepared with polyolefin infusions bags (Easyflex). However, due to an Easyflex shortage, Viaflo infusion bags were used and cyclophosphamide (CPM) concentrations showed a 10% increase despite a similar manufacturing process. The objectives of this work were to study the influence of different containers on CPM concentrations measured by FIA and to investigate the origin of this artificial increase in concentration. Methods: Thirty infusions were prepared using 3 different infusion bags: Viaflo multilayer container, Ecoflac, low-density polyethylene, and Easyflex polyolefin bags. Vials of CPM 1 g were reconstituted with 50 mL of 0.9% sodium chloride. CPM was injected into 0.9% sodium chloride 250-mL infusion bags. Then 1 mL samples were withdrawn to be analyzed by FIA, to determine CPM concentrations (ultraviolet detection at 205 nm). Results: Mean CPM concentration values (n = 10) were 3.52 mg/mL for Viaflo infusions, 3.12 mg/mL for Ecoflac infusions, and 3.16 mg/mL for Easyflex infusions. CPM concentrations were higher in Viaflo infusion bags. This difference could be explained by ε-caprolactam, a component released by the multilayer infusion bag. Conclusion: Viaflo infusion bags disturb outcomes of CPM dosage with a concentration artificially increased by about 10%. The FIA method cannot be used to quantify CPM at this concentration and at wavelength 205 nm.